Low pressure sintering method of titanium carbonitride based cermet
Patent Information
- Application Number
- CN202611391829.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-09
AI Technical Summary
真空烧结所得烧结体中容易残留孔隙;提高烧结温度虽可减少孔隙,但会促进硬质相晶粒长大
[0017](1)采用钛、钨、钼、钽和铬的氧化物与炭黑作为反应原料,使反应物料逆氮气流向连续通过碳热还原氮化反应区,并对反应产物进行氮气保护冷却、气流粉碎和分级,能够制得平均粒径为0.6~0.9 μm、氧含量和游离碳含量均低于0.4 wt.%的(Ti,W,Mo,Ta,Cr)(C,N)单相固溶体粉;
Smart Images

Figure CN122879540A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal ceramics preparation technology, and specifically to a low-pressure sintering method for titanium carbonitride-based metal ceramics. Background Technology
[0002] Titanium carbonitride-based cermets typically use Ti(C,N) as the main hard phase, with metals such as Co and Ni as binder phases, and refractory metal carbides such as Mo₂C and WC added. The process involves mixing, forming, and liquid-phase sintering. During liquid-phase sintering, the hard phase dissolves and precipitates within the liquid metal binder phase, forming a core-ring structure. The porosity of the sintered body, the composition and morphology of the core-ring structure, and the grain size of the hard phase all affect the material's strength and toughness.
[0003] Existing technologies typically use Ti(C,N) powder and various refractory metal carbide powders separately as feedstocks. Due to the different dissolution and precipitation behaviors of each hard phase component during liquid-phase sintering, the resulting core-ring structure is not easily homogeneous in composition and morphology. To improve the distribution of elements in the hard phase, existing technologies use carbonitride solid solution powders containing multiple metal elements as the hard phase raw material. These solid solution powders can be prepared by carbothermic reduction nitridation reactions of corresponding metal oxides and carbon sources. The reaction products are then pulverized and classified for use in the preparation of metal ceramics. Carbothermic reduction nitridation products often exhibit agglomeration; the reaction conditions and subsequent pulverization and classification affect the phase composition, particle size, oxygen content, and free carbon content of the resulting solid solution powder.
[0004] Titanium carbonitride-based cermets are typically produced by vacuum sintering or pressure sintering. Vacuum sintering often results in residual porosity in the sintered body; while increasing the sintering temperature can reduce porosity, it also promotes the growth of hard phase grains. Pressure sintering can further improve the densification of the sintered body, but existing pressure sintering processes mainly reduce porosity by increasing the sintering temperature or gas pressure, resulting in insufficient control over the growth of hard phase grains, and thus the flexural strength and fracture toughness of the resulting sintered body are still affected. Summary of the Invention
[0005] The purpose of this invention is to provide a low-pressure sintering method for titanium carbonitride-based cermets to obtain multi-component single-phase solid solution powder with controlled particle size and impurity content, and to control the growth of hard phase grains while improving the densification of the sintered body.
[0006] To achieve the above objectives, the present invention provides a low-pressure sintering method for titanium carbonitride-based cermets, comprising the following steps: S1. Mix titanium oxide powder, tungsten oxide powder, molybdenum oxide powder, tantalum oxide powder and chromium oxide powder with carbon black to obtain the reaction material. S2. Nitrogen gas is flowed through the carbothermic reduction nitridation reaction zone, and the reactants are continuously passed through the reaction zone in the opposite direction to the nitrogen gas flow to obtain the carbothermic reduction nitridation product. S3. After the carbothermic reduction nitridation product is cooled, it is subjected to air jet milling and classification using nitrogen or argon to obtain a single-phase solid solution powder with an average particle size of 0.6 to 0.9 μm. S4. The single-phase solid solution powder is wet-milled with Mo2C powder, Co powder and Ni powder. The resulting slurry is dried, a forming agent is added and granulated, and then pressed to form a compact. S5. Degrease the compact under vacuum conditions, and after degreasing, continue to heat it to 1400°C under vacuum conditions; S6. After the vacuum temperature is raised to 1400℃, argon gas is introduced into the sintering furnace to make the argon gas pressure in the furnace reach 1-3 MPa. Liquid phase sintering is carried out at 1400℃ and the argon gas pressure in the furnace is maintained at 1-3 MPa throughout the liquid phase sintering and holding period. When the liquid phase sintering holding is completed and the cooling begins, the argon pressure in the furnace is increased to 4 MPa, and the sintered body is cooled under the argon pressure of 4 MPa to obtain titanium carbonitride-based metal ceramics.
[0007] In one embodiment, in step S1, the titanium oxide powder is TiO2 powder, the tungsten oxide powder is WO3 powder, the molybdenum oxide powder is MoO3 powder, the tantalum oxide powder is Ta2O5 powder, and the chromium oxide powder is Cr2O3 powder.
[0008] In one embodiment, the molar ratio of TiO2 powder, WO3 powder, MoO3 powder, Ta2O5 powder and Cr2O3 powder is (0.85-0.92):(0.05-0.10):(0.02-0.05):(0.005-0.015):(0.001-0.005), and the amount of carbon black added is 102%-105% of the theoretical carbon content.
[0009] In one embodiment, in step S2, the temperature of the carbothermic reduction nitriding reaction zone is 1600–1800°C, and the residence time of the reactants in the carbothermic reduction nitriding reaction zone is 3–5 h.
[0010] In one embodiment, in step S3, nitrogen is used as the working gas for airflow pulverization and classification, the airflow pulverization pressure is 0.6 to 1.0 MPa, and the classification wheel speed is 3000 to 4000 r / min.
[0011] In one embodiment, in step S3, the oxygen content of the (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder is less than 0.4 wt.%, and the free carbon content is less than 0.4 wt.%.
[0012] In one embodiment, in step S4, the forming agent is polyethylene glycol, and the amount of polyethylene glycol added is 1% to 3% of the total mass of the single-phase solid solution powder, Mo2C powder, Co powder and Ni powder; the pressing pressure is 100 to 150 MPa, and the holding time is 5 to 20 s.
[0013] In one embodiment, in step S4, the mass fraction of the Mo2C powder is 3% to 8% by mass percentage, and the total mass fraction of the Co powder and Ni powder is 10% to 16%; the mass ratio of the Co powder to the Ni powder is 1:1.
[0014] In one embodiment, in step S6, the liquid phase sintering holding time is 40 to 90 minutes, and the argon pressure in the furnace is maintained at 1.5 to 2.5 MPa throughout the liquid phase sintering holding period.
[0015] In one embodiment, the liquid phase sintering holding time is 60 min, and the argon pressure in the furnace is maintained at 2 MPa throughout the liquid phase sintering holding period.
[0016] Compared with the prior art, the beneficial effects of this application are as follows:
[0017] (1) Using oxides of titanium, tungsten, molybdenum, tantalum and chromium and carbon black as reaction raw materials, the reaction materials are continuously passed through the carbothermic reduction nitriding reaction zone against the nitrogen flow direction, and the reaction products are subjected to nitrogen protection cooling, airflow pulverization and classification, which can produce (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder with an average particle size of 0.6-0.9 μm and oxygen content and free carbon content of less than 0.4 wt.%; (2) Using the above-mentioned single-phase solid solution powder and maintaining an argon pressure of 1-3 MPa throughout the liquid phase sintering process at 1400℃, combined with 4 MPa argon pressure cooling after the end of the heat preservation, can improve the densification of the sintered body, control the growth of hard phase grains, and make the sintered body have good bending strength and Palmqvist fracture toughness. Attached Figure Description
[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0019] Figure 1 This is a process flow diagram of the low-pressure sintering method of the present invention.
[0020] Figure 2 The images are: (a) Scanning electron microscope image, particle size distribution map, and X-ray diffraction pattern of (Ti,W,Mo,Ta,Cr)(C,N) solid solution powder; (b) Scanning electron microscope image and particle size distribution map of submicron-sized (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1; (c) Scanning electron microscope image and particle size distribution map of micron-sized (Ti,W,Mo,Ta,Cr)(C,N) solid solution powder with an average particle size of 2.25 μm; (d) X-ray diffraction pattern of submicron-sized (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1.
[0021] Figure 3 (a) Backscattered electron diagrams of titanium carbonitride-based metal ceramics obtained at different vacuum sintering temperatures; (b) Backscattered electron diagrams of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1000℃. (b) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1100℃; (c) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1200℃; (d) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1300℃; (e) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1400℃; (f) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1450℃; (g) Backscattered electron diagram of titanium carbonitride-based metal ceramics obtained under vacuum sintering and holding conditions at 1500℃.
[0022] Figure 4 X-ray diffraction patterns of titanium carbonitride-based metal ceramics obtained under different liquid phase sintering conditions; (a) X-ray diffraction pattern of titanium carbonitride-based metal ceramics obtained under vacuum liquid phase sintering and heat preservation conditions. (b) is the X-ray diffraction pattern of titanium carbonitride-based metal ceramics obtained under liquid-phase sintering and holding conditions at 1 MPa argon pressure; (c) is the X-ray diffraction pattern of titanium carbonitride-based metal ceramics obtained under liquid-phase sintering and holding conditions at 2 MPa argon pressure; (d) is the X-ray diffraction pattern of titanium carbonitride-based metal ceramics obtained under liquid-phase sintering and holding conditions at 3 MPa argon pressure; (e) is the X-ray diffraction pattern of titanium carbonitride-based metal ceramics obtained under liquid-phase sintering and holding conditions at 4 MPa argon pressure.
[0023] Figure 5 The images show the backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under different liquid-phase sintering conditions: (a) Backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under vacuum liquid-phase sintering and holding conditions; (b) Backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under 1 MPa argon pressure liquid-phase sintering and holding conditions; (c) Backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under 2 MPa argon pressure liquid-phase sintering and holding conditions; (d) Backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under 3 MPa argon pressure liquid-phase sintering and holding conditions; (e) Backscattered electron microscopy (PRF) diagrams and hard phase grain size distribution diagrams of titanium carbonitride-based cermets obtained under 4 MPa argon pressure liquid-phase sintering and holding conditions.
[0024] Figure 6 This is a diagram showing the density and relative density of titanium carbonitride-based cermets obtained under different liquid-phase sintering conditions.
[0025] Figure 7 The diagrams show the flexural strength, Vickers hardness, and Palmqvist fracture toughness of titanium carbonitride-based cermets obtained under different liquid-phase sintering conditions.
[0026] Figure 8 The image shows the indentation crack propagation morphology of titanium carbonitride-based cermets obtained by liquid-phase sintering at 1400℃ and 4 MPa argon pressure. Detailed Implementation
[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] The process flow of this invention is as follows: Figure 1As shown, the process includes reactant preparation, continuous carbothermic reduction nitriding, reaction product cooling, air jet milling and classification, wet ball milling, pressing and forming, vacuum degreasing and heating, low-pressure liquid phase sintering and pressurized cooling.
[0029] Example 1
[0030] This embodiment provides a method for preparing titanium carbonitride-based metal ceramics. First, a (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder is prepared. Then, using the obtained single-phase solid solution powder as the hard phase raw material, liquid-phase sintering is performed under argon pressure to obtain titanium carbonitride-based metal ceramics. The specific steps include: (1) Weigh 702.8 g of TiO2 powder, 162.3 g of WO3 powder, 43.2 g of MoO3 powder, 33.1 g of Ta2O5 powder, 3.8 g of Cr2O3 powder, and 347.0 g of carbon black. Place the above raw materials, anhydrous ethanol, and cemented carbide balls in a ball mill jar. The mass ratio of cemented carbide balls to the above raw materials is 8:1. Wet ball mill at 80 r / min for 48 h. After ball milling, vacuum dry the resulting slurry to obtain the reaction material.
[0031] The molar ratio of TiO2, WO3, MoO3, Ta2O5 and Cr2O3 is 0.880∶0.070∶0.030∶0.0075∶0.0025, and the amount of carbon black added is equivalent to 103% of the theoretical carbon content.
[0032] (2) The reactants obtained in step (1) are loaded into multiple graphite boats, and each graphite boat is sequentially fed into the carbothermic reduction nitriding reaction apparatus. The temperature of the carbothermic reduction nitriding reaction zone is 1800℃, and the graphite boats pass through the reaction zone at a speed of 5 mm / min, so that the residence time of the reactants in the reaction zone is 4 h.
[0033] Nitrogen gas with a purity of 99.99% is introduced from the discharge end to the feed end of the carbothermic reduction nitriding reactor at a flow rate of 3 L / min, so that the flow direction of the nitrogen gas is opposite to the movement direction of the graphite boat, thereby obtaining the carbothermic reduction nitriding product.
[0034] (3) Cool the carbothermic reduction nitridation product obtained in step (2) to room temperature in a nitrogen atmosphere. Use nitrogen as the working gas to perform air jet milling and classification on the cooled carbothermic reduction nitridation product. The air jet milling pressure is 0.8 MPa and the classifier speed is 3500 r / min. Collect the powder obtained from the classification.
[0035] The obtained powder had an average particle size of 0.86 μm, an oxygen content of 0.33 wt.%, and a free carbon content of less than 0.4 wt.%. Under the X-ray diffraction detection conditions used, no other crystalline phases were detected except for the diffraction peaks of the (Ti,W,Mo,Ta,Cr)(C,N) solid solution. The obtained powder was recorded as (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder.
[0036] (4) Weigh 820.0 g of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder, 50.0 g of Mo2C powder, 65.0 g of Co powder and 65.0 g of Ni powder obtained in step (3), place them in a ball mill jar, add industrial alcohol and cemented carbide balls, and wet ball mill at 70 r / min for 72 h. The mass ratio of cemented carbide balls to powder raw materials is 8:1.
[0037] After ball milling, the resulting slurry was vacuum dried at 60°C for 12 h. A 20% (w / w) polyethylene glycol alcohol solution was prepared and added to the dried mixed powder. The actual amount of polyethylene glycol added was 2.0% of the total mass of the powder raw materials. After stirring and mixing for 30 min, the mixture was granulated through a 60-mesh sieve and then vacuum dried at 60°C for 8 h to obtain a shaped mixture. The shaped mixture was loaded into a mold and subjected to bidirectional pressing at 120 MPa for 10 s to obtain a compact.
[0038] (5) Place the pressed blank obtained in step (4) into a vacuum-low pressure integrated sintering furnace and pump the furnace pressure to no more than 10 Pa; under continuous vacuum conditions, heat up to 550°C at a heating rate of 2°C / min and hold at 550°C for 60 min; then continue heating up to 1400°C at a heating rate of 5°C / min.
[0039] (6) After the sintering furnace temperature reaches 1400℃, maintain the furnace temperature at 1400℃ and introduce argon gas into the sintering furnace to make the argon gas pressure in the furnace reach 2 MPa. Start calculating the liquid phase sintering holding time when the argon gas pressure in the furnace reaches 2 MPa, and hold at 1400℃ and 2 MPa argon gas pressure for 60 min.
[0040] When the liquid-phase sintering holding period ends and the sintering furnace temperature begins to decrease, the argon pressure inside the furnace is increased from 2 MPa to 4 MPa, and maintained at 4 MPa during the cooling process. After the sintered body cools to room temperature, the pressure is released and the material is removed from the furnace, yielding titanium carbonitride-based cermet.
[0041] Example 2
[0042] Take the same batch of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1, prepare a compact according to steps (4) and (5) of Example 1 and heat it to 1400℃.
[0043] The difference between this embodiment and Embodiment 1 is that, at the beginning of the liquid phase sintering holding period, the argon pressure inside the furnace is brought to 1 MPa and maintained at this pressure throughout the entire 60-minute liquid phase sintering holding period. When the liquid phase sintering holding period ends and cooling begins, the argon pressure inside the furnace is increased to 4 MPa, and cooling is performed at 4 MPa argon pressure. All other conditions are the same as in Embodiment 1.
[0044] Example 3
[0045] Take the same batch of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1, prepare a compact according to steps (4) and (5) of Example 1 and heat it to 1400℃.
[0046] The difference between this embodiment and Embodiment 1 is that, at the beginning of the liquid phase sintering holding period, the argon pressure inside the furnace is brought to 3 MPa and maintained at this pressure throughout the entire 60-minute liquid phase sintering holding period. When the liquid phase sintering holding period ends and cooling begins, the argon pressure inside the furnace is increased to 4 MPa, and cooling is performed at 4 MPa argon pressure. All other conditions are the same as in Embodiment 1.
[0047] Comparative Example 1 Take the same batch of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1, prepare a compact according to steps (4) and (5) of Example 1 and heat it to 1400℃.
[0048] The compact was subjected to liquid-phase sintering at 1400℃ for 60 min, with a vacuum maintained during the holding period and no argon gas introduced into the sintering furnace. After the liquid-phase sintering holding was completed and cooling began, argon gas was introduced into the sintering furnace to bring the argon gas pressure inside the furnace to 4 MPa, and cooling was performed under this 4 MPa argon gas pressure. All other conditions were the same as in Example 1.
[0049] Comparative Example 2 Take the same batch of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1, prepare a compact according to steps (4) and (5) of Example 1 and heat it to 1400℃.
[0050] At the start of the liquid phase sintering hold, the argon pressure inside the furnace was brought to 4 MPa and maintained at this pressure throughout the entire 60-minute liquid phase sintering hold. After the hold was completed, cooling continued at an argon pressure of 4 MPa. All other conditions were the same as in Example 1.
[0051] Comparative Example 3 Take a single-phase solid solution powder (Ti,W,Mo,Ta,Cr)(C,N) with the same powder composition and particle size as obtained in step (3) of Example 1, and prepare a compact according to step (4) of Example 1. Place the obtained compact in a vacuum-low pressure integrated sintering furnace and evacuate the furnace pressure to no more than 10 Pa; under continuous vacuum conditions, heat to 550°C at a heating rate of 2°C / min and hold at 550°C for 60 min; then continue heating to 1000°C at a heating rate of 5°C / min and hold at 1000°C under vacuum for 60 min. When the holding time ends and cooling begins, argon gas is introduced into the sintering furnace to make the argon gas pressure in the furnace reach 4 MPa, and cooling is performed under 4 MPa argon gas pressure.
[0052] Comparative Example 4 The difference between this comparative example and comparative example 3 is that the sintering holding temperature is 1100℃, while the other conditions are the same as those in comparative example 3.
[0053] Comparative Example 5 The difference between this comparative example and comparative example 3 is that the sintering holding temperature is 1200℃, while the other conditions are the same as those in comparative example 3.
[0054] Comparative Example 6 The difference between this comparative example and comparative example 3 is that the sintering holding temperature is 1300℃, while the other conditions are the same as those in comparative example 3.
[0055] Comparative Example 7 The difference between this comparative example and comparative example 3 is that the sintering holding temperature is 1450℃, while the other conditions are the same as those in comparative example 3.
[0056] Comparative Example 8 The difference between this comparative example and comparative example 3 is that the sintering holding temperature is 1500℃, while the other conditions are the same as those in comparative example 3.
[0057] Comparative Example 9 The powder raw materials, compact preparation, sintering temperature, total holding time, and cooling conditions in this comparative example are the same as in Example 1. The difference lies in the timing of the application of 2 MPa argon pressure: after the compact reaches 1400°C and begins liquid phase sintering, a vacuum is maintained for the first 30 minutes; when the holding time reaches 30 minutes, argon is introduced into the sintering furnace to bring the argon pressure inside the furnace to 2 MPa, and this pressure is maintained for the next 30 minutes; when the liquid phase sintering holding time ends and cooling begins, the argon pressure inside the furnace is increased to 4 MPa, and cooling is performed under 4 MPa argon pressure.
[0058] The powders and sintered samples obtained from the examples and comparative examples were tested using the following methods.
[0059] The average particle size was determined by observing the powder morphology using a scanning electron microscope, and the size of no fewer than 100 powder particles was statistically analyzed using image analysis software. The average particle size was taken as the average particle size. The oxygen content of the powder was determined using a nitrogen-oxygen analyzer, and the free carbon content was determined according to the method specified in GB / T 5124.2—2008.
[0060] The phase composition of the powder and sintered samples was detected by X-ray diffraction with a tube voltage of 40 kV and a tube current of 30 mA. Cu-Kα radiation was used, and the scanning range 2θ was 20° to 90°.
[0061] The density of the sintered samples was determined according to GB / T 3850—2015, and the relative density was the ratio of the measured density to the theoretical density calculated based on the actual powder formulation; the flexural strength was determined according to GB / T 3851—2015; the HV30 Vickers hardness was determined according to GB / T 7997—2014; and the Palmqvist fracture toughness was determined according to ISO 28079:2009.
[0062] After grinding and polishing the sintered sample, the microstructure was observed using the backscattered electron mode of a scanning electron microscope. The size of no less than 100 hard phase grains in each group was statistically analyzed using image analysis software to obtain D10, D50 and D90.
[0063] Scanning electron microscope images and particle size distribution diagrams of the submicron-sized (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1 are shown below. Figure 2 As shown in (a), the X-ray diffraction pattern is as follows: Figure 2 As shown in (c). Another micron-sized (Ti,W,Mo,Ta,Cr)(C,N) solid solution powder with an average particle size of 2.25 μm was selected as a reference powder. Its scanning electron microscope image and particle size distribution diagram are shown below. Figure 2 As shown in (b).
[0064] Depend on Figure 2 (a) It can be seen that the average particle size of the powder obtained in step (3) of Example 1 is 0.86 μm, while the average particle size of the reference powder is 2.25 μm. Figure 2 (c) It can be seen that, apart from the diffraction peaks of the (Ti,W,Mo,Ta,Cr)(C,N) solid solution, no other crystalline phase diffraction peaks appeared in the powder obtained in step (3) of Example 1.
[0065] The above results show that, according to the continuous carbothermal reduction nitriding, nitrogen atmosphere cooling, airflow pulverization and classification process described in steps (1) to (3) of Example 1 of this application, submicron-sized multi-component single-phase solid solution powder for subsequent forming and low-pressure liquid phase sintering can be prepared.
[0066] The backscattered electron pattern of the sintered sample obtained from the vacuum sintering temperature screening test is shown below. Figure 3 As shown, where Figure 3 (a)~ Figure 3 (g) corresponds to vacuum sintering and heat preservation conditions of 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1450℃ and 1500℃ respectively.
[0067] Depend on Figure 3 It is evident that as the sintering holding temperature increases from 1000℃ to 1400℃, the porosity in the sintered body gradually decreases. In the vacuum sintering temperature screening test, the relative density of the sintered body obtained at 1400℃ was 96.5%, and the flexural strength was 1282 MPa. When the sintering holding temperature was further increased to 1450℃ and 1500℃, the number of larger hard phase grains in the microstructure increased, and the flexural strength decreased. Therefore, this application determines the liquid phase sintering temperature to be 1400℃ and applies different argon pressures at this temperature.
[0068] Examples 1-3 and Comparative Examples 1-2 used the same batch of (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder obtained in step (3) of Example 1, and adopted the same powder ratio, wet ball milling conditions, forming conditions, sintering temperature, holding time, and cooling pressure. The difference was the argon pressure in the furnace during the liquid phase sintering holding at 1400℃. The X-ray diffraction results of the sintered samples obtained in each group are as follows: Figure 4 As shown, where Figure 4 (a)~ Figure 4 (e) Corresponding to vacuum, 1 MPa, 2 MPa, 3 MPa and 4 MPa liquid phase sintering heat preservation conditions, respectively, are Comparative Example 1, Example 2, Example 1, Example 3 and Comparative Example 2.
[0069] Depend on Figure 4 It is evident that the (Ti,M)(C,N) hard phase is the main crystalline phase in all groups of sintered samples, where M represents W, Mo, Ta, and Cr. Under the testing conditions employed, no significant changes were observed in the main crystalline phase of each group of sintered samples.
[0070] The backscattered electron microscopy (PRK) images and hard phase grain size distributions of the sintered samples obtained in Examples 1-3 and Comparative Examples 1-2 are shown below. Figure 5 As shown in Table 1, the statistical results of the hard phase grain size are presented.
[0071] Table 1. Statistical results of hard phase grain size under different liquid phase sintering holding pressures.
[0072] As shown in Table 1, the D90 of the sintered bodies obtained under vacuum, 1 MPa, 2 MPa, 3 MPa, and 4 MPa conditions are 1.02 μm, 1.21 μm, 1.36 μm, 1.40 μm, and 1.46 μm, respectively. (Combined with...) Figure 5 It can be seen that as the liquid phase sintering holding pressure increases, the large-diameter end of the hard phase grain size distribution gradually increases; under the conditions of 3 MPa and 4 MPa, the number of larger hard phase grains in the microstructure increases.
[0073] The densities and relative densities of the sintered samples obtained in Examples 1-3 and Comparative Examples 1-2 are as follows: Figure 6 As shown, compared with vacuum sintering, the density and relative density of the sintered body were generally increased after applying argon pressure during liquid-phase sintering at 1400℃. Specifically, the relative density of the sintered body obtained under 2 MPa conditions was 97.4%, and the relative density of the sintered body obtained under 4 MPa conditions was 97.8%.
[0074] The flexural strength, HV30 Vickers hardness, and Palmqvist fracture toughness of the sintered specimens obtained in Examples 1-3 and Comparative Examples 1-2 are as follows: Figure 7 As shown, with the increase of liquid-phase sintering holding pressure, both the flexural strength and Palmqvist fracture toughness show a change of first increasing and then decreasing. The flexural strength of the sintered body obtained under the condition of 2 MPa is 2237 MPa, and the Palmqvist fracture toughness is 10.5 MPa·m. 1 / 2 The HV30 Vickers hardness of the sintered body obtained under 4 MPa conditions is 1698, but its bending strength and Palmqvist fracture toughness are both lower than those of the sintered body obtained under 2 MPa conditions.
[0075] Combining Table 1 and Figure 5 It can be seen that the D90 of the sintered body obtained under 4 MPa conditions is 1.46 μm, and the number of larger hard phase grains in the microstructure increases. The indentation crack propagation morphology of the sintered sample obtained in Comparative Example 2 is as follows. Figure 8 As shown. By Figure 8 It is evident that the indentation crack penetrates some of the larger hard phase grains during its propagation, indicating that the larger hard phase grains participate in the crack propagation process. This crack propagation morphology corresponds to the results of increased D90, decreased flexural strength, and decreased Palmqvist fracture toughness under 4 MPa conditions.
[0076] comprehensive Figures 5-8As shown in Table 1, compared with vacuum sintering, applying an argon pressure of 1–3 MPa during liquid-phase sintering at 1400℃ generally improves the densification of the sintered body. When the liquid-phase sintering holding pressure is increased to 4 MPa, although the relative density and hardness of the sintered body are further improved, it is accompanied by an increase in larger hard phase grains, and the bending strength and Palmqvist fracture toughness are lower than those of the sintered body obtained under the condition of 2 MPa. Therefore, under the tested conditions, controlling the liquid-phase sintering holding pressure at 1–3 MPa can balance the densification of the sintered body and the control of the hard phase grain size, among which the sintered body obtained under the condition of 2 MPa has higher bending strength and Palmqvist fracture toughness.
[0077] To investigate the effect of the timing of applying 2 MPa argon pressure on the sintering results, Example 1 and Comparative Example 9 used the same powder raw materials, compact preparation conditions, sintering temperature, total holding time, and cooling conditions. The only difference was the timing of applying 2 MPa argon pressure during the liquid phase sintering holding at 1400℃. The sintered samples obtained from both examples were tested, and the results are shown in Table 2.
[0078] Table 2. Test results at different 2 MPa argon pressure application times.
[0079] As shown in Table 2, compared with Comparative Example 9, the relative density of Example 1 increased by 0.5 percentage points, the flexural strength increased by 357 MPa, and the Palmqvist fracture toughness increased by 0.8 MPa·m. 1 / 2 The D90 increased by 0.07 μm. The flexural strength and fracture toughness of the sintered body are affected by factors such as the degree of densification and the grain size of the hard phase. In this comparison, the D90 of Example 1 increased by only 0.07 μm, while the relative density, flexural strength and Palmqvist fracture toughness were all improved. This indicates that applying 2 MPa from the beginning of liquid phase sintering is beneficial to improving the densification, flexural strength and Palmqvist fracture toughness of the sintered body, while keeping the increase in the grain size of the hard phase within a small range.
[0080] The above description is merely a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Equivalent substitutions or modifications made based on the disclosure of the present invention are all within the scope of protection of the present invention.
Claims
1. A low-pressure sintering method for titanium carbonitride-based cermets, characterized in that, Includes the following steps: S1. Mix titanium oxide powder, tungsten oxide powder, molybdenum oxide powder, tantalum oxide powder and chromium oxide powder with carbon black to obtain the reaction material. S2. Nitrogen gas is flowed through the carbothermic reduction nitridation reaction zone, and the reactants are continuously passed through the reaction zone in the opposite direction to the nitrogen gas flow to obtain the carbothermic reduction nitridation product. S3. After the carbothermic reduction nitridation product is cooled, it is subjected to air jet milling and classification using nitrogen or argon to obtain a (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder with an average particle size of 0.6-0.9 μm. S4. The single-phase solid solution powder is wet-milled with Mo2C powder, Co powder and Ni powder. The resulting slurry is dried, a forming agent is added and granulated, and then pressed to form a compact. S5. Degrease the compact under vacuum conditions, and after degreasing, continue to heat it to 1400°C under vacuum conditions; S6. After the vacuum temperature is raised to 1400℃, argon gas is introduced into the sintering furnace to make the argon gas pressure in the furnace reach 1-3 MPa. Liquid phase sintering is carried out at 1400℃ and the argon gas pressure in the furnace is maintained at 1-3 MPa throughout the liquid phase sintering and holding period. When the liquid phase sintering holding is completed and the cooling begins, the argon pressure in the furnace is increased to 4 MPa, and the sintered body is cooled under the argon pressure of 4 MPa to obtain titanium carbonitride-based metal ceramics.
2. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S1, the titanium oxide powder is TiO2 powder, the tungsten oxide powder is WO3 powder, the molybdenum oxide powder is MoO3 powder, the tantalum oxide powder is Ta2O5 powder, and the chromium oxide powder is Cr2O3 powder.
3. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 2, characterized in that, The molar ratio of TiO2 powder, WO3 powder, MoO3 powder, Ta2O5 powder and Cr2O3 powder is (0.85~0.92):(0.05~0.10):(0.02~0.05):(0.005~0.015):(0.001~0.005), and the amount of carbon black added is 102%~105% of the theoretical carbon content.
4. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S2, the temperature of the carbothermic reduction nitriding reaction zone is 1600–1800°C, and the residence time of the reactants in the carbothermic reduction nitriding reaction zone is 3–5 h.
5. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 4, characterized in that, In step S3, nitrogen is used as the working gas for air jet milling and classification. The air jet milling pressure is 0.6 to 1.0 MPa, and the classifier speed is 3000 to 4000 r / min.
6. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S3, the oxygen content of the (Ti,W,Mo,Ta,Cr)(C,N) single-phase solid solution powder is less than 0.4 wt.%, and the free carbon content is less than 0.4 wt.%.
7. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S4, the forming agent is polyethylene glycol, and the amount of polyethylene glycol added is 1% to 3% of the total mass of the single-phase solid solution powder, Mo2C powder, Co powder and Ni powder; the pressing pressure is 100 to 150 MPa, and the holding time is 5 to 20 s.
8. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S4, based on the total mass of the single-phase solid solution powder, Mo2C powder, Co powder and Ni powder as 100%, the mass fraction of Mo2C powder is 3% to 8%, the total mass fraction of Co powder and Ni powder is 10% to 16%, and the mass ratio of Co powder to Ni powder is 1:
1.
9. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 1, characterized in that, In step S6, the liquid phase sintering holding time is 40 to 90 minutes, and the argon pressure in the furnace is maintained at 1.5 to 2.5 MPa throughout the liquid phase sintering holding period.
10. The low-pressure sintering method for titanium carbonitride-based cermets according to claim 9, characterized in that, The liquid phase sintering holding time was 60 min, and the argon pressure in the furnace was maintained at 2 MPa throughout the liquid phase sintering holding period.